2022
DOI: 10.1089/apc.2022.0035
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Stigma and Health-Related Quality of Life Among People Living with HIV in Northern Thailand

Abstract: HIV-related stigma and discrimination have been a significant barrier to accessing health care, hence contributing to poor health outcomes. This study aimed to investigate factors associated with HIV-related stigma and discrimination and health-related quality of life (HRQoL) among people living with HIV in rural Thailand setting. A cross-sectional convenience sample of 161 HIV-positive Thai patients was recruited from a single rural district hospital using a self-administered questionnaire entailing sociodemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
5
2
Order By: Relevance
“…We observed the positive changes among student nurses who had provided nursing for PLWHA, from negative attitudes and misconceptions to struggling and conflicting psychology in care-giving, and then to positive perceptions after care-giving. Before care-giving, student nurses presented fear, stigma, and discrimination toward HIV-infected patients, which may impact patient care [30,31]. This is consistent with previous research that people are often afraid of contracting what they perceive as a deadly virus [32] and may choose to avoid exposure to PLWHAs because of a lack of information about HIV transmission [33].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We observed the positive changes among student nurses who had provided nursing for PLWHA, from negative attitudes and misconceptions to struggling and conflicting psychology in care-giving, and then to positive perceptions after care-giving. Before care-giving, student nurses presented fear, stigma, and discrimination toward HIV-infected patients, which may impact patient care [30,31]. This is consistent with previous research that people are often afraid of contracting what they perceive as a deadly virus [32] and may choose to avoid exposure to PLWHAs because of a lack of information about HIV transmission [33].…”
Section: Discussionsupporting
confidence: 70%
“…Before care-giving, student nurses presented fear, stigma, and discrimination toward HIV-infected patients, which may impact patient care [ 30 , 31 ]. This is consistent with previous research that people are often afraid of contracting what they perceive as a deadly virus [ 32 ] and may choose to avoid exposure to PLWHAs because of a lack of information about HIV transmission [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disclosure of HIV infection in this study was 71.6%, higher than other studies ( 21 , 83 ). The majority of participants chose to disclose to their spouses (58.9%) and children (46.7%), and a small proportion disclosed the disease to parents (19.6%) and friends (7.4%).…”
Section: Discussioncontrasting
confidence: 69%
“…Second, nearly half of the PLWH in this sample had received only primary education and below, and their cognitive level of mental health might not be sufficient ( 86 ). Last, previous studies have shown that disclosure, sexual orientation and other factors have a significant impact on the mental health of PLWH ( 87 ), the level of disclosure in this sample population is higher than that in previous studies ( 21 , 83 ), and the sexual orientation is mostly heterosexual. It would be easier to tap into special populations such as men who have sex with men (MSM), sexual service providers or adolescent groups to identify the relevant influencing factors.…”
Section: Discussioncontrasting
confidence: 55%
“…Poorer HRQoL in people living with HIV has been consistently associated with several factors. These include stigma and low social support [9,10], depression and stress, lower socioeconomic status, lower educational status, sexual dissatisfaction, lower self-esteem, being female, being heterosexual, having acquired HIV through intravenous drug use, and living longer with HIV [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%